ANALISA PROJECT MANAGEMENT TERHADAP PRODUK ECO ENZYME - Delvian Yosuky; Vincent Linardo; Tio Sania Rachmi; Felix Santono (Universitas 17 Agustus 1945, 2022)
Eco Enzyme is a result of organic waste fermentation, derived from leftover fruits, vegetables, sugar, and water. It was first discovered by Dr. Rosukon Poompanvong, a member of the Organic Farming Association from Thailand. Eco Enzyme serves as a versatile liquid for household, agricultural, and livestock purposes. According to an article by Vama & Chekar in 2020, eco enzyme can be utilized as an antifungal, antibacterial, insecticide agent, and cleaner. Some of its functions include being a floor cleaner, dish cleaner, and toilet cleaner.The author created a business around eco enzyme using leftover fruits. The raw materials for eco enzyme are obtained from fruits that are no longer consumable or have become spoiled. Although there have been numerous studies on utilizing leftover fruits for eco enzyme production, not many people in the community are aware of or use eco enzyme. Therefore, the author came up with the idea of a business centered around eco enzyme, both as a value proposition for utilizing leftover fruits and as a means to educate people who are unfamiliar with eco enzyme.